Surface analysis and shear bond strength of zirconia on resin cements after non-thermal plasma treatment and/or primer application for metallic alloys - Vechiato-Filho, Aljomar José [UNESP]; Matos, Adaias Oliveira; Landers, Richard; Goiato, Marcelo Coelho [UNESP]; Rangel, Elidiane Cipriano [UNESP]; De Souza, Grace Mendonça; Barão, Valentim Adelino Ricardo; dos Santos, Daniela Micheline [UNESP] (Elsevier, 2017)
There is no established protocol for bonding zirconia (Y-TZP) with resin cements. Non-thermal plasma (NTP) may be an alternative for the clinical problems related to adhesion. The purpose of the present study was to characterize the surface of Y-TZP exposed to methane (CH4) NTP or coated with a layer of primer for metal alloys and the association between the two methods and to evaluate the effect of NTP treatment on bond strength between Y-TZP and two resin cements. A total of 235 Y-TZP discs (8 × 2 mm) were distributed into five groups: Co (no surface treatment), Pr (primer), NTP (methane plasma), Pr + NTP and NTP + Pr. The effect of the treatment type on the surface free energy, morphology, topography and chemical composition of the Y-TZP discs was investigated. The discs were cemented to composite resin substrates using Panavia F2.0 or RelyX U200. Shear bond strength (n = 10) analyses were performed (1 mm/min) before and after thermocycling (5–55 °C, 2000 cycles) on the bonded specimens. The data were analyzed with one and three-way ANOVAs and Bonferroni tests (α = 0.05). NTP reduced the surface energy and roughness of the Y-TZP discs. SEM-EDS and XPS analyses showed the presence of the organic thin film, which significantly improved the bond strength results when Rely X U200 was used, whereas the primer treatment was more effective with Panavia F2.0. Thermocycling significantly reduced the bond strength results of the NTP and Pr + NTP groups cemented with Rely X U200 and the Pr and NTP + Pr groups cemented with Panavia F2.0. Nonthermal plasma improves the bond strength between Rely X U200 and Y-TZP and also seems to have water-resistant behavior, whereas Panavia F2.0 showed better results when associated with primer.
Keywords: Bond strength; Resin cement; Zirconia